Sinergi Relasi Sosial dan Inovasi Digital dalam Pemberdayaan UMKM Sebuah Studi Komunitas Naik Kelas Lampung - Imam Mahmud; Erna Rochana; Azis Ahmad; Teuku Fahmi (Jurnal Community, 2026)
The research examines the empowerment of Micro, Small and Medium Enterprises (MSMEs) that are often hampered by challenges in the business management process, adoption of digital technology and limited social networks. Aiming to analyze the relationship between social relations and digital innovation on MSME empowerment, the research study focuses on the strategic role of the Lampung Upscale MSME Community as a partner supporting the development of MSMEs in Lampung Province. A descriptive qualitative approach was used with data collected through observation, interviews and documentation of activities carried out by the community. The results showed that the Lampung Upscale MSME Community has 227 members (215 micro, 12 small, and 0 medium) spread across 11 districts or cities with the highest dominance of MSMEs engaged in the food sector. This community conducts social media management training and capacity building for MSME products offline or online, as well as providing assistance and market access among members. The utilization of social relations and digital innovation has proven effective in supporting various community activities, thus increasing the competitiveness of MSMEs in Lampung. However, the results of the study identified that the social network that was built was not fully optimal due to the obstacles of a wide area coverage and weak coordination between local, central and community government institutions, making it difficult for MSME actors to recognize the role of each stakeholder in the program that MSME actors wanted to encourage.